Influence of excited molecules N₂(A³Σu⁺), N₂(B³Πg), O₂(¹Δg) and O₂(b¹Σg⁺) on ozone and hydroxyls (H₂O₂, OH, HO₂) kinetics in the plasma of barrier discharge in air at atmospheric pressure - Kalyuzhnaya, A.G.; Tsiolko, V.V. (Вопросы атомной науки и техники, 2015)
The kinetics of the N₂(A³Σu⁺), N₂(B³Πg), O₂(¹Δg) and O₂(b¹Σg⁺) excited states in the barrier-discharge plasma in atmospheric air is calculated and their effect on the concentrations of derivative products – ozone and hydroxyls OH, НO₂ and H₂O₂ is analyzed. It is shown that the largest deviations in the concentrations obtained with and without taking into account the excited states are observed for H₂O₂ (≈60%) and О₃ (≈ 40%) at a relative humidity of 20%. The variation of the air humidity from 20…80% does not result in qualitative changes in the behavior of the ozone and hydroxyl concentrations in the barrier discharge. Рассчитана кинетика возбужденных уровней N₂(A³Σu⁺), N₂(B³Πg), O₂(¹Δg) И O₂(b¹Σg⁺) в барьерном разряде в воздухе и проанализировано их влияние на концентрации озона и гидроксилов OH, НO₂ и H₂O₂. Показано, что максимальное расхождение в концентрациях, полученных с учетом возбужденных состояний и без них, составляет около 60% для H₂O₂ и 40% для О₃ при влажности 20%. Варьирование влажности воздуха от 20…80% не приводит к качественному изменению поведения концентраций озона и гидроксилов в разряде. Проведено розрахунки кінетики збуджених станів N₂(A³Σu⁺), N₂(B³Πg), O₂(¹Δg) та O₂(b¹Σg⁺) у бар’єрному розряді в повітрі та проаналізовано їх вплив на концентрації озону та гідроксилів OH, НO₂ та H₂O₂. Показано, що максимальне розходження в концентраціях, отриманих із врахуванням збуджених станів та без них, становить близько 60% для H₂O₂ та 40% для О₃ при вологості 20%. Варіювання вологості в межах від 20…80% не призводить до якісної зміни поведінки концентрацій озону та гідроксилів у розряді.